20 Years of TIMSS: Lessons for Indonesia - LUSCHEI, THOMAS F (Indonesian Research Journal in Education |IRJE|, 2017)
The Trends in International Mathematics and Science Study (TIMSS) has been administered to countries around the world every four years since 1995, generating rich cross-national data on school resources and student achievement that can inform policy and classroom practice. Although Indonesia has participated in every round of TIMSS, there is very little published research in English drawing educational lessons from these data for Indonesia. In this article, I described Indonesia’s performance on TIMSS over time and relative to other countries. Reviewing TIMSS reports on mathematics and science, I offered both positive and negative lessons from Indonesia’s participation in TIMSS since 1995.